New Evidence on Active Ageing in Europe - Alan Walker; Asghar Zaidi (Intereconomics, 2016)
Ensuring active ageing, i.e. the optimisation of opportunities for health, participation and security in order to enhance quality of life as people age, is an important growth strategy for the EU. Achieving a successful active ageing policy will require a sea change in thinking about what ageing means in both economic and social terms.
Keywords: 330; Alternde Bevölkerung; Lebensqualität; Seniorenpolitik; EU-Staaten